THE EVALUATION OF TEACHER’S COMPETENCE IN ENGLISH LEARNING AT SMK-PP NEGERI SAREE - maulizan Za; Khatmi (Yayasan Almubarak Fil Ilmi, 2021)
The purpose of this study was to describe the competence of teachers teaching English in terms of competence in learning management, namely lesson planning, learning implementation, assessment of learning outcomes, and implementation of follow-up learning outcomes. In analyzing the data used inequality evaluation model. The research subjects were English teachers at the Saree State Vocational High School. The results of the study indicate that the teacher has planned an interesting, creative, innovative learning plan and is in accordance with the time allocation and according to the characteristics of the students; in the implementation of learning, English teachers have implemented effective learning in accordance with the time allocation; in assessing learning outcomes, teachers have not used the learning outcomes assessment instruments in the lesson plans; while in the follow-up of learning outcomes, teachers have not used student learning outcomes to make further lesson plans.